Safeguarding Investor Rights: OJK’s Regulatory Framework Including Management and Challenges in Indonesia’s Capital Market - Kusnawirawan, Iwan; Syarkani, Yofi; Hernayati, Hernayati; Waluyo, Imam (Jurnal Multidisiplin Indonesia, 2025)
Investor protection is crucial for maintaining stability and trust in Indonesia’s capital market. The Financial Services Authority (Otoritas Jasa Keuangan, OJK) plays a central role in regulating transparency, preventing fraud, and providing dispute resolution mechanisms. Despite a robust regulatory framework, challenges such as weak enforcement, low financial literacy, and regulatory inefficiencies persist. This study employs a qualitative research approach, incorporating legal analysis and a management control framework. Primary data includes expert interviews, while secondary data consists of financial reports, journal articles, and regulatory documents. Key Performance Indicators (KPIs) such as enforcement actions, fraud detection rates, and investor restitution are analyzed to evaluate regulatory effectiveness. Fraud Prevention through POJK No. 43/POJK.04/2020, which grants OJK the authority to impose sanctions but struggles with enforcement effectiveness; and (3) Alternative Dispute Resolution via collaboration with LAPS SJK and the APPK platform, which enhances accessibility but faces challenges in public awareness and efficiency. Despite these measures, issues such as inadequate deterrents for market violations, gaps in technological supervision, and bureaucratic inefficiencies hinder optimal investor protection. To strengthen investor protection, OJK must enhance legal enforcement, expand financial literacy programs, leverage technology for market supervision, and improve inter-agency coordination. The adoption of RegTech solutions, blockchain transparency mechanisms, and stricter legal sanctions can significantly boost regulatory efficiency and investor confidence. Future research should explore international best practices to further refine Indonesia’s financial regulatory landscape.